High throughput screening identifies ATP-competitive inhibitors of the NLRP1 inflammasome. Issue 14 (15th July 2015) - Harris, Philip A.; Duraiswami, Chaya; Fisher, Donald T.; Fornwald, James; Hoffman, Sandra J.; Hofmann, Glenn; Jiang, Ming; Lehr, Ruth; McCormick, Patricia M.; Nickels, Leng; Schwartz, Benjamin; Wu, Zining; et al.
Graphical abstract